Les pays les moins avancés rapport 2015 - United Nations Conference on Trade; Development (United Nations, 2016)
This report documents the importance of the rural sector and agriculture in least developed countries (LDCs), through their contribution to employment generation and economic activity, as well as the fact that the bulk of LDC poverty is concentrated in rural areas. The discussion is placed in the perspective of the post-2015 development agenda, in which rural economic transformation will be a sine qua non for sustainable rural poverty eradication. It presents evidence on agricultural productivity dynamics in LDCs, discussing the importance of agricultural productivity for human development in rural areas, and analysing the key elements driving agricultural productivity growth in these countries. It examines the synergies and complementarities between agricultural productivity growth and rural economic diversification. It concludes by discussing the policies which need to be put in place to accelerate agricultural productivity and diversify rural economies, thereby providing the essential contribution to reaching LDCs’ development goals.